KUALITAS TIDUR DAN KEPARAHAN STROKE ISKEMIK - Ester Saripati Harianja; Amila Amila; Salmawati Salmawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Stroke is a major cause of disability and death worldwide. Impaired sleep quality in recent years has been seen as a potential factor causing stroke. Inadequate quality and quantity of sleep can impair memory and cognitive abilities. The aim of the study was to determine the relationship between sleep quality and ischemic stroke severity at Haji Adam Malik Hospital in Medan. This type of research is analytic correlation with a cross sectional approach. All patients treated in the Neurology Room of H. Adam Malik General Hospital Medan were used as research subjects with inclusion and exclusion criteria of 30 people. Sleep quality was measured using the PSQI questionnaire. Stroke severity was measured using the NIHSS score sheet. Data were analyzed using The Chi square test with a significance reference of p<0.05. The results showed that the majority of the respondents had poor sleep quality, 25 (83.3%), stroke severity, the majority of respondents were severe, 15 (50%). The results of statistical tests showed that there was a relationship between sleep quality and ischemic stroke severity at H. Adam Malik General Hospital with p value = 0.00. It is recommended to carry out further research on differences in sleep quality before and after a stroke, especially in relation to activities of daily living.